Peran Dinas Kebudayaan, Kepemudaan, Olahraga Dan Pariwisata Dalam Memfasilitasi Sanggar Tari Di Kabupaten Mojokerto - Salsabila Nurmaulidya; Ananta Prathama (JURNAL ILMIAH ILMU ADMINISTRASI, 2025)
The Indonesian nation is a nation rich in arts and culture. Traditional Indonesian dance as one form of culture that is a national heritage must be preserved and its authenticity maintained. Mojokerto Regency is one of the relics of the Majapahit kingdom that has many cultural heritages. The Department of Culture, Youth, Sports, and Tourism (Disbudporapar) plays an important role in preserving traditional dance by facilitating dance studios. This study aims to examine the role of Disbudporapar in facilitating dance studios as an effort to preserve traditional dance in Mojokerto Regency. The methods in this study use literature reviews, interviews, and observations. Informants consist of the Head of Culture, studio owners, and dancers involved in studio activities. The results of the study are guided by the principle of the role of local government according to Iyas Yusuf which shows that Disbudporapar plays a role as a regulator, facilitator, and dynamic in the development of dance studios. As a regulator, Disbudporapar establishes policies that support the preservation of traditional dance. As a facilitator, they provide support in the form of funding, providing necessary infrastructure. As a dynamic, Disbudporapar encourages community participation and collaboration with various parties to increase awareness and interest in traditional dance. Through these roles, Disbudporapar contributes significantly to increasing awareness and interest in traditional dance, thus supporting the sustainability and development of local culture.